The influence of urban heat towards pedestrian comfort and the potential use of plants and water as heat ameliorator in Kuala Lumpur city centre area - Mohammed, Siti Zakiah (2004)
Kuala Lumpur, like other cities in a tropical environment faces serious environmental degradation of urban heat island, atmospheric pollution, traffic congestion and high energy consumption due to its rapid development and urbanisation. Unlike cities with a cool temperate climate and made worse by being in a valley set up, Kuala Lumpur outdoor living comfort is seriously affected by accumulation of heat and generation of dust and smoke. All these have resulted in a decrease in outdoor living comfort and quality, making outdoor life quite miserable, deterioration in public health and is even life threatening. This thesis aims to provide a basis for understanding and create awareness on the importance of comfortable outdoor living environment for comfortable human life and living with serious attention on issues of urban heat and the effective use of natural elements such as plants and water as heat ameliorator. This will hopefully be a new tool to the city managers, planners, architects, engineers and even landscape architects to integrate the concern of their built environment with sustainable natural landscape development toward sustainable and comfortable outdoor living environment. This thesis is based on data obtained from survey questionnaires, site observations,field measurements and professional interviews. The data were analysed as to determine the needs and preferences of the outdoor users towards their outdoor comfort. Interviews were being justified through site observations and field measurements. Relevant professional groups were interviewed to gauge their understanding and views on their current approaches in planning, designing and managing the city outdoor environment. The results showed that the temperature and humidity readings taken at vegetated and densely built-up areas in Kuala Lumpur city, showed a difference of an increase of 5°C to 8°C temperature and a reduction of 10% to 14% humidity. The general public displayed a lack of understanding and awareness on the impact of heat to their outdoor comfort. The professionals gave priority to requirements and guidelines in their own professional area rather than looking at the urban environment in total during the designing and implementation stage.The research recommends continuous massive tree-planting programmes,encouragement of more vertical landscape or rooftop gardens and more moving water features to be the basis to ameliorate the urban heat while the professionals should integrate the their built environment with sustainable natural eco system. Political leaders, policy makers and the public need to understand and be more aware of the issue of the outdoor living comfort and how nature can help to comfort mankind and sustain a good outdoor living environment.